KETERKAITAN PERUBAHAN PENGGUNAAN LAHAN INDUSTRI DENGAN PRODUK DOMESTIK REGIONAL BRUTO SEKTOR INDUSTRI DI KABUPATEN BEKASI - Kintan Aulia Fabriani; Anita Sitawati; Sugihartoyo Sugihartoyo (Universitas Trisakti, 2021)
The land is a strategic natural resource for development. The need for land for different development sectors creates opportunities for land-use changes. Bekasi Regency is one of the Jakarta buffer areas and has been designated as an industrial zone. With this stipulation, the land-use change for Industry keeps increasing in Bekasi Regency. The changes in land use from non-built land to built land can be characterized as one of the characteristics of land-use changes in urban areas. On the other hand, land-use change can be associated with economic growth. In the regional scope, economic growth is measured based on the amount of Gross Regional Domestic Product. In line with this, in Bekasi Regency, there is a deceleration of economic growth and the value of gross regional domestic product. The purpose of this study is to examine the relationship between industrial land-use changes and industrial sector of the gross regional domestic product in Bekasi Regency in 2011 - 2020. The method used to analyze in this study is quantitative descriptive analysis and correlation analysis. The results of the study have shown that the growth of the industrial land area has no relationship with the growth of industrial sector of the gross regional domestic product, which is indicated by a negative correlation result.